Donald Trump’s Alternative Facts Re-shaping National and International Discourses: The Big D. Analysis - Atolagbe, Adebukunola Agnes (Advances in Social Sciences Research Journal, 2017)
The author aims to interprete saying and doing in terms of identity, by examining the Inaugural Speech of President Donald Trump of the United States of America, and relate the use of language by political leaders, albeit all leaders, to the immediate and wider contexts of their speeches. This is particularly relevant in a globalised world, where the power of language and its use can have far reaching effects, and issues thrown up resonating with different categories of people, as with the particular discourse in focus. James Paul Gee’s concept of the ‘Big D’ in Discourse Analysis (D/discourse Analysis) is employed in this qualitative study.